1994
DOI: 10.1152/jn.1994.71.6.2236
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of pH in rat brain synaptosomes. I. Role of sodium, bicarbonate, and potassium

Abstract: 1. We investigated the regulation of intracellular pH (pHi) in rat brain isolated nerve terminals (synaptosomes), using fluorescence pH indicators and time-resolved fluorescence spectroscopy. 2. The resting pHi was not significantly affected by the presence or absence of HCO3-. Removal of external Na+, in the absence or presence of HCO3- caused a rapid acidification of pHi. The recovery from acid loads was primarily due to the activity of the Na+/H+ exchanger, confirming the relevance of this transport system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 0 publications
2
29
1
Order By: Relevance
“…An important system regulating intracellular Na ϩ concentrations is the Na ϩ -H ϩ -exchanger, which can be specifically inhibited by amiloride and several of its analogues (Grinstein and Rothstein 1986;Frelin et al 1988). Na ϩ -H ϩ -exchangers have also been identified on brain cell membranes and synaptosomes (Kalaria et al 1998;Sauvaigo et al 1984;Sanchez-Armass et al 1994). Inhibition by amiloride or amiloride derivatives re- duces synaptosomal Na ϩ uptake leading to a reduced free intracellular Na ϩ concentration (Sauvaigo et al 1984;Liu et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…An important system regulating intracellular Na ϩ concentrations is the Na ϩ -H ϩ -exchanger, which can be specifically inhibited by amiloride and several of its analogues (Grinstein and Rothstein 1986;Frelin et al 1988). Na ϩ -H ϩ -exchangers have also been identified on brain cell membranes and synaptosomes (Kalaria et al 1998;Sauvaigo et al 1984;Sanchez-Armass et al 1994). Inhibition by amiloride or amiloride derivatives re- duces synaptosomal Na ϩ uptake leading to a reduced free intracellular Na ϩ concentration (Sauvaigo et al 1984;Liu et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Cytosolic pH was determined by fluorescence of intracellular Pyranine (8-hydroxy pyrene-1,3,6,trisulfonic acid) as previously described [3]. The dye was loaded in the resealed membrane vesicles during the first homogenization step in 0.32 M sucrose solution containing 10 mM Pyranine.…”
Section: Fluorescence Measurementsmentioning
confidence: 99%
“…In mammalian isolated presynaptic nerve terminals (synaptosomes), the Na + /H + exchanger has been the only unequivocally demonstrated H + -transporting mechanism in the synaptosomal preparation [1][2][3][4]. Regarding the Cl -/ HCO 3 -exchanger, previous data [2,5] indicated that there was no experimental evidence supporting the participation of HCO 3 --based transport mechanisms in synaptosomes, even though the neuronal somas posses one or more types of Cl -/HCO 3 -exchangers [6][7][8][9], in addition to the Na + /H + exchanger.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These buffers were supplemented with 6.8 ÌM of nigericin and 2 ÌM valinomycin to collapse the H + and K + gradients. Collapsing of the H + and K + gradients is essential, since it has been shown that certain cell types exhibit changes in pH in upon A23187 treatment [17,26]. To evaluate the in situ sensitivity of MagFura-2, cells were co-loaded with high-and low-affinity Ca 2+ probes.…”
Section: In Situ Calibration Of Mag-fura-2mentioning
confidence: 99%